2010
DOI: 10.1007/s00122-010-1517-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.)

Abstract: Cultivated groundnut or peanut (Arachis hypogaea L.), an allotetraploid (2n = 4x = 40), is a self pollinated and widely grown crop in the semi-arid regions of the world. Improvement of drought tolerance is an important area of research for groundnut breeding programmes. Therefore, for the identification of candidate QTLs for drought tolerance, a comprehensive and refined genetic map containing 191 SSR loci based on a single mapping population (TAG 24 × ICGV 86031), segregating for drought and surrogate traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
169
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 55 publications
13
169
4
2
Order By: Relevance
“…However, the scatter diagrams of Figure 4 showed that there was still some variation in pod yield besides those explained by the relative HI. Therefore, these residual pod yield unexplained by the % HI component were computed as the difference between the actual pod yields and the predicted pod yield using the regression equation between pod weight and the relative HI, following previous work (Vadez et al 2007b;2011). These residuals were then plotted against TE and showed a very tight relationship under the mild DS-1 stress (R 2 = 0.41), whereas there was a non-significant relation in the other two DS treatments (R 2 = 0.15 in DS-2; R 2 = 0.14 in DS-3) (data not shown).…”
Section: Water Uptake and Te Relationship With Yield Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the scatter diagrams of Figure 4 showed that there was still some variation in pod yield besides those explained by the relative HI. Therefore, these residual pod yield unexplained by the % HI component were computed as the difference between the actual pod yields and the predicted pod yield using the regression equation between pod weight and the relative HI, following previous work (Vadez et al 2007b;2011). These residuals were then plotted against TE and showed a very tight relationship under the mild DS-1 stress (R 2 = 0.41), whereas there was a non-significant relation in the other two DS treatments (R 2 = 0.15 in DS-2; R 2 = 0.14 in DS-3) (data not shown).…”
Section: Water Uptake and Te Relationship With Yield Componentsmentioning
confidence: 99%
“…Twenty genotypes were tested and included thirteen breeding lines-cultivars Chico, CSMG 84-1, ICG (FDRS) 10, ICG S 44, ICGS 76, ICGV 00350, ICGV 86015, ICGV 86031, ICGV 91114, ICR 48, JL 24, TAG 24, TMV 2 and seven recombinant inbreed lines (RILs) of a cross between TAG 24 and ICGV 86031, which was previously assessed for mapping drought related QTLs (Krishnamurthy et al 2007;Ravi et al 2011).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…For example, the first SSRbased genetic linkage map for cultivated groundnut was recently developed for the mapping population, TAG 24 × ICGV 86031 (Varshney et al, 2009b). Subsequently five more genetic maps were developed based on mapping populations segregating for drought and foliar diseases (Gautami et al, 2012a;Ravi et al, 2011;Sujay et al, 2012). A consensus map for drought tolerance related traits with 293 SSR loci (Gautami et al, 2012a) and foliar disease resistance with 225 SSR loci (Sujay et al, 2012), respectively have been developed.…”
Section: Comprehensive Genetic Maps Andmentioning
confidence: 99%
“…The SSR-based cultivated genetic map with 135 marker loci developed by Varshney et al (2009) was then further saturated to 191 SSR loci (Ravi et al, 2011). Two new partial genetic maps with 56 (TAG 24 3 GPBD 4) and 45 (TG 26 3 GPBD 4) marker loci (Khedikar et al, 2010;Sarvamangala et al, 2011) were constructed covering a genetic distance of 462.24 and 657.9 cM, respectively.…”
Section: Recent Advancement In Genetic Linkage Mapsmentioning
confidence: 99%